The effect of breast massage training on self-efficacy and perceived stress of prim parous women: A clinical trial study - Somayeh Ramezani; Omid Garkaz; Ahmad Khosravi; Zohra Ghasemi; Sahar Paryab; Nahid Bolbolhaghighi (Wolters Kluwer Medknow Publications, 2023)
Background: Breastfeeding is a highly efficacious, health-promoting activity that prevents many disorders and diseases. Successful breastfeeding depends on various maternal physiological and psychological factors, among which breastfeeding self-efficacy is an adjustable framework. This study investigates the effect of breast massage training on self-efficacy and perceived stress in primiparous women. Materials and Methods: This study is a clinical trial study on 132 eligible primiparous mothers referred to Bahar Hospital from August 15, 2019, to December 15, 2020. The women were randomly divided into intervention and control groups. The massage was performed in the intervention group before breastfeeding. The data were collected using a standard breastfeeding self-efficacy questionnaire and the Sheldon Perceived Standard Questionnaire. Data were entered into SPSS 18 and analyzed using descriptive statistics, Chi-square, and analysis of variance. Results: The results of this study showed that the mean (SD) breastfeeding self-efficacy in the breast massage training group with direct midwife involvement was 61.63 (9.21), higher than the one in the control group 51.51 (11.62). In addition, perceived stress was 19.81 in the intervention group and 24.84 in the control group, which was also statistically significant. Conclusions: Due to the increase in self-efficacy scores and decrease in stress scores after breast massage, this method can improve breastfeeding performance in women. Therefore, educational strategies should be developed in this area.